1995
DOI: 10.7326/0003-4819-123-1-199507010-00002
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive Ganciclovir Therapy To Prevent Cytomegalovirus Disease in Cytomegalovirus Antibody-Positive Renal Transplant Recipients

Abstract: Preemptive ganciclovir therapy administered daily during courses of treatment with antilymphocyte antibodies reduced the excessive occurrence of cytomegalovirus disease in renal transplant recipients who were positive for cytomegalovirus antibody. This approach, which links the most potent immunosuppression to intensive antimicrobial therapy, allows preventive therapy to be given to those patients at greatest risk for developing infectious complications. These patients are likely to benefit most from the preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(97 citation statements)
references
References 0 publications
4
92
0
1
Order By: Relevance
“…This strategy has been reported to be successful in renal transplant recipients. 23 Similar studies have also been performed in different transplant recipients (Table 5).…”
Section: Prophylaxis With Antiviral Agentssupporting
confidence: 54%
See 1 more Smart Citation
“…This strategy has been reported to be successful in renal transplant recipients. 23 Similar studies have also been performed in different transplant recipients (Table 5).…”
Section: Prophylaxis With Antiviral Agentssupporting
confidence: 54%
“…Likewise, acute fulminant hepatitis, an additional independent risk factor for CMV disease after OLT, is associated with significant release of inflammatory cytokines. 21 Lastly, such situations as stress secondary to prolonged intra-abdominal surgery or bacterial infections, which are associated with increased levels of lipopolysaccharides, could explain their epidemiological association with an increased risk for CMV disease [22][23][24][25][26][27] (Table 1).…”
Section: Pathogenesismentioning
confidence: 99%
“…The incidence and severity of CMV disease are also influenced by the amount of immunosuppression used (188)(189)(190)(191). Chemoprophylaxis for CMV (with acyclovir, ganciclovir, valacyclovir and/or intravenous immunoglobulin) has been shown to be effective in large, randomized controlled trials (192)(193)(194)(195)(196)(197)(198). A meta-analysis of controlled trials also concluded that antiviral agents (acyclovir or ganciclovir) were effective in preventing CMV infection in solid-organ transplant recipients (199).…”
Section: Rationalementioning
confidence: 99%
“…The impetus behind prolonged treatment is an increasing recognition of late CMV disease. Two studies evaluated ganciclovir in patients who received antilymphocyte antibody therapy demonstrated a reduction in CMV disease (Hibberd et al, 1995;KDIGO, 2009). Accordingly, the use of intravenous ganciclovir or oral valganciclovir has been recommended for CMV prophylaxis during antilymphocyte antibody therapy (1).…”
Section: Chemoprophylaxismentioning
confidence: 99%